2015
DOI: 10.1371/journal.pone.0122710
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Levels in Children Aged 0–6 Years Old in Hunan Province, China from 2009–2013

Abstract: ObjectivesThe aim of this study is to describe blood lead levels (BLLs) and the prevalence of elevated blood lead levels (EBLLs) in children aged 0–6 years old and to analyze the BLL trend in children from 2009 to 2013 in China.MethodsA total of 124,376 children aged 0–6 years old were recruited for this study from January 1st 2009 to December 31st 2013. Their blood lead levels were analyzed using atomic absorption spectrometry.ResultsThe median BLL was 64.3 μg/L (IQR: 49.6–81.0), and the range was 4.3–799.0 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…We used capillary blood instead of venous blood because obtaining it is less invasive, minimizes pain, requires smaller amounts of blood volume, and the procedure can be performed quickly and easily [24]. Furthermore, it has been found that capillary blood sample collection by fingerstick has very low (<10%) contamination error rates [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used capillary blood instead of venous blood because obtaining it is less invasive, minimizes pain, requires smaller amounts of blood volume, and the procedure can be performed quickly and easily [24]. Furthermore, it has been found that capillary blood sample collection by fingerstick has very low (<10%) contamination error rates [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The response rate in our study was high (80%) which may be due to counseling parents about the study, providing a free test which is otherwise not available as a regular test in Nepal, and distributing lead test results to parents. We used capillary blood instead of venous blood because obtaining it is less invasive, minimizes pain, requires smaller amounts of blood volume, and the procedure can be performed quickly and easily [ 24 ]. Furthermore, it has been found that capillary blood sample collection by fingerstick has very low (<10%) contamination error rates [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when analyzing the epidemiological data, Li et al found that BLLs declined in children aged 0–18 years from 1990 to 2012 [ 16 ]. By 2013, the BLLs of children aged 0–6 years in Hunan Province were only 20 μ g/L [ 19 ]. Similarly, the BLLs of children in Shanghai in 2014 were much lower than the earlier reported data [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a substantial increase in the number of small family businesses that use lead-containing products has occurred in this region in recent years. As a result, despite the overall decline in children's BLLs in China over the past 10 years [ 16 , 19 , 23 ], children's exposure to lead is still common in Taizhou.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 40 years, blood lead levels (BLL) in children have fallen dramatically, worldwide, probably due to the removal of lead from petrol, paints and other manufactured products [6], together with specific measures to limit its harmful effects [7,8]. However, population-based studies continue to report the presence of toxic levels of lead in children [4,9]. In developing or underdeveloped countries, its prevalence remains high, and so health problems persist.…”
Section: Introductionmentioning
confidence: 99%